2015
DOI: 10.1104/pp.114.255430
|View full text |Cite
|
Sign up to set email alerts
|

Network of GRAS Transcription Factors Involved in the Control of Arbuscule Development inLotus japonicus   

Abstract: (P.-M.D.) Arbuscular mycorrhizal (AM) fungi, in symbiosis with plants, facilitate acquisition of nutrients from the soil to their host. After penetration, intracellular hyphae form fine-branched structures in cortical cells termed arbuscules, representing the major site where bidirectional nutrient exchange takes place between the host plant and fungus. Transcriptional mechanisms underlying this cellular reprogramming are still poorly understood. GRAS proteins are an important family of transcriptional regu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
175
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 154 publications
(196 citation statements)
references
References 105 publications
(142 reference statements)
10
175
0
Order By: Relevance
“…These data are in accordance with the "birdsfoot" arbuscules described by Gutjahr and Parniske (2013) Feddermann et al, 2010), RAM2 (Wang et al, 2012), VAMP72s (Ivanov et al, 2012), SYP132A (Pan et al, 2016), EXO70I (Zhang et al, 2015), VTI12 (Lota et al, 2013), ERF1 (Devers et al, 2013), RED (Groth et al, 2013;Gutjahr and Parniske, 2013), RAM1/ATA (Rich et al, 2015), RAD1 (Park et al, 2015;Xue et al, 2015), and FatM (Bravo et al, 2016). Hence, P inhibition may be related to the functions of these genes.…”
Section: The Potential Mechanism Of P Inhibitionsupporting
confidence: 73%
“…These data are in accordance with the "birdsfoot" arbuscules described by Gutjahr and Parniske (2013) Feddermann et al, 2010), RAM2 (Wang et al, 2012), VAMP72s (Ivanov et al, 2012), SYP132A (Pan et al, 2016), EXO70I (Zhang et al, 2015), VTI12 (Lota et al, 2013), ERF1 (Devers et al, 2013), RED (Groth et al, 2013;Gutjahr and Parniske, 2013), RAM1/ATA (Rich et al, 2015), RAD1 (Park et al, 2015;Xue et al, 2015), and FatM (Bravo et al, 2016). Hence, P inhibition may be related to the functions of these genes.…”
Section: The Potential Mechanism Of P Inhibitionsupporting
confidence: 73%
“…Moreover, GRAS proteins have been reported to form homodimers and heterodimers with other GRAS family members and this is likely important for their transcriptional regulation function (Itoh et al, 2002;Cui et al, 2007;Heo et al, 2011;Zhang et al, 2011;Gobbato et al, 2012;Murakami et al, 2013;Xue et al, 2015). Here, our structure of Os-SCL7 was determined in a dimer with helices A12, A79, and A69 at the dimer interface.…”
Section: Discussionmentioning
confidence: 99%
“…They play important regulatory roles in a number of plant processes including signaling, development, abiotic stress, and symbiosis [22] [27]. Recent works demonstrated a direct involvement of several GRAS transcription factors in both mycorrhizal signaling and colonization, namely NSP1, NSP2, RAM1, DELLA, DELLA-interacting protein (DIP1) and RAD1 [15] Here, we focused on a rice GRAS protein previously identified by a whole transcriptome analysis as being specifically expressed in rice mycorrhizal roots and silent in response to mock treatment [34]. No further functional characterization of this GRAS protein, named OsAM18, is available so far.…”
Section: Resultsmentioning
confidence: 99%
“…The massive reorganization described in AM colonized plants requires a unique transcriptional program [7] which induces changes associated with metabolic pathways controlling nutritional exchanges, cell wall modifications, secondary metabolism, signal transduction, and protein turn-over [8]- [14]. On the basis of a RNAseq analysis, Xue and colleagues showed that 45 genes encoding transcriptional factors (TFs) or transcriptional regulators were significantly up-regulated in Lotus japonicus mycorrhizal roots when compared with non-mycorrhizal roots [15]. These genes belong to the main TFs families and include GRAS, AP2/ERF, NO APICAL MERISTEM, ARABIDOPSIS TRANSCRIPTION ACTIVATION FACTOR, CUP-SHAPED COTYLEDON (NAC)-domain, MADS, MYB, C2H2 zinc finger, bZIP, ARF, WRKY DNA binding domain, NIN-like protein and LOB domain.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation